2011
DOI: 10.1126/science.1197636
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Erosion and Restoration of Mars’ Northern Polar Dunes

Abstract: Despite radically different environmental conditions, terrestrial and martian dunes bear a strong resemblance, indicating that the basic processes of saltation and grainfall (sand avalanching down the dune slipface) operate on both worlds. Here, we show that martian dunes are subject to an additional modification process not found on Earth: springtime sublimation of Mars' CO(2) seasonal polar caps. Numerous dunes in Mars' north polar region have experienced morphological changes within a Mars year, detected in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
133
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 203 publications
(139 citation statements)
references
References 23 publications
6
133
0
Order By: Relevance
“…Thus, signs of contemporary dune mobility on Martian dunes are required to validate their use as indicators of present-day wind direction, but only if the activity is consistent with the morphological interpretation of wind direction. Indeed, many signs of isolated present-day aeolian transport are apparent on Mars (Bridges et al, 2007;Sullivan et al, 2008;Reiss et al, 2010;Silvestro et al, 2010;Hansen et al, 2011). However, evidence of widespread, present-day dune activity and migration is thus far limited.…”
Section: Extra-terrestrial Dunesmentioning
confidence: 99%
See 4 more Smart Citations
“…Thus, signs of contemporary dune mobility on Martian dunes are required to validate their use as indicators of present-day wind direction, but only if the activity is consistent with the morphological interpretation of wind direction. Indeed, many signs of isolated present-day aeolian transport are apparent on Mars (Bridges et al, 2007;Sullivan et al, 2008;Reiss et al, 2010;Silvestro et al, 2010;Hansen et al, 2011). However, evidence of widespread, present-day dune activity and migration is thus far limited.…”
Section: Extra-terrestrial Dunesmentioning
confidence: 99%
“…Silvestro et al (2010) showed evidence of ripple migration on the surface of dunes in the Nili Patera and inferred dune migration from changes in the dune base-ground surface contact and in the development of streaks representing grainflows on the slipface. More recently, Hansen et al (2011) showed that the morphology of northern polar dunes on Mars is modified by seasonal sublimation of CO 2 and aeolian sediment transport. Collectively, the evidence suggests aeolian saltation is occurring; however, there remains some uncertainty as to whether the dunes are actively modified by aeolian erosion and deposition, or if the observed changes are simply an effect of sediment bypassing over indurated (crusted) dunes (cf.…”
Section: Extra-terrestrial Dunesmentioning
confidence: 99%
See 3 more Smart Citations